2018
DOI: 10.1089/cap.2017.0085
|View full text |Cite
|
Sign up to set email alerts
|

Atomoxetine, Parent Training, and Their Effects on Sleep in Youth with Autism Spectrum Disorder and Attention-Deficit/Hyperactivity Disorder

Abstract: ATX appears sleep neutral. Clinicians who treat ADHD symptoms in children and adolescents with ASD may prefer ATX over psychostimulants when sleep disturbance is an issue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…[ 57 ] Methylphenidate, modafinil and other psychostimulants are effective in the management of these sleep disorders. [ 58 ] Dysregulation of NREM sleep leads to narcolepsy only, whereas; Dys-regulation of REM sleep leads combined narcolepsy with cataplexy. [ 59 ] It has been reported that orexin increases vigilance through increases awaking time and decreases REM and NREM sleep periods.…”
Section: Role Of Orexin In Psychiatric Disordersmentioning
confidence: 99%
“…[ 57 ] Methylphenidate, modafinil and other psychostimulants are effective in the management of these sleep disorders. [ 58 ] Dysregulation of NREM sleep leads to narcolepsy only, whereas; Dys-regulation of REM sleep leads combined narcolepsy with cataplexy. [ 59 ] It has been reported that orexin increases vigilance through increases awaking time and decreases REM and NREM sleep periods.…”
Section: Role Of Orexin In Psychiatric Disordersmentioning
confidence: 99%
“…Atomoxetine is less likely to cause insomnia and other sleep issues, and can be considered as a second-choice option. 195,196 Guanfacine and clonidine induce sedation, and may be used alone or in combination with stimulants. [197][198][199] Prescribing a treatment such as melatonin to specifically address sleep issues may be needed in certain individuals.…”
Section: Depressionmentioning
confidence: 99%
“…Many hypotheses regarding the cause of sleep problems among ASD patients include anxiety, related brain pathologies, and an inability to regulate the sleep hormone melatonin. Sleep disturbances among children with ASD are associated with inadequate melatonin secretion [6-9]. This problem is an important feature that affects social communication, daily life, daytime functioning and behavior, and quality of life and increases parental sleep disruption and stress.…”
Section: Introductionmentioning
confidence: 99%
“…Medication use for sleep disorders is common among children with ASD [12]. Various studies have reported the useful effects of medications such as melatonin for the treatment of sleep disorders among children with ASD [1,6,7]. To date, a structured review study of randomized controlled trials of drug interventions used to treat sleep disorders in patients with ASD.…”
Section: Introductionmentioning
confidence: 99%